Antenna design using dynamic multi-objective evolutionary algorithm - Jiao, Ruwang; Sun, Yongzhi; Sun, Jianqing; Jiang, Yuhong; Zeng, Sanyou (IET microwaves, antennas & propagation, 2018)
To enhance the robustness and stability of the antenna design, a novel methodology is presented for modelling the antenna design problem as the constrained optimisation problem (COP). Then a framework is introduced for solving the COP. The framework converts a COP into an equivalent dynamic constrained multi-objective optimisation problem (DCMOP). A dynamic constrained multi-objective evolutionary algorithm is applied to address the transformed DCMOP, which means the COP as well as the antenna design problem can be solved. Then it is applied to design three classes of antennas: a wire antenna, a patch antenna and an antenna array. Obtained results of these three kinds of antenna suggest that the proposed methods can well satisfy the antenna design requirements.